?SYNTHESIS OF SOME HETROCYCLES FROM DEHYDRO-L-ASCORBIC ACID AND THEIR BIOLOGICAL ACTIVITY - MANCY, SOHILA H.; SEKILY, MOHAMED A. EL; DAGHFAG, HAGER AL; ALI, O M KOLTIIOOM A. (Biological Sciences - PJSIR, 1994)
Sythesis of some hetrocyc1ic compouds from dehydro-L-ascorbic acid, monoaryl hydrazone and their biological activities are described.